Fundamentals of jurisprudence of Sheikh Al-Shirazi in matters of command - Aboubacar, Karamoko (Journal of Islamic Sciences, 2021)
The present study aimed at identifying the views of Sheikh Al-Shirazi on the fundamentals of jurisprudence related to matters of command and his objections to his opponents through his books. To achieve the goal of the study, the researcher relied on analytical method as a research methodology. After addressing the topics of the study in its general framework, the researcher reached many conclusions, including: Sheikh Al-Shirazi objected to many scholars of Usul al-Fiqh regarding matters of the command, and he has several methods of objection in this regard, including: the clear statement by mentioning the names of some of his opponents, such as Abu al-Qasim al-Balkhi, and the method of indicating without mentioning names of others such as saying: Some of the Shaafa’is, some of the companions of Abu Hanifa, and some Mu’tazilites said. The expressions of objections that al-Shirazi used against the scholars of Usul al-Fiqh in matters of command were mentioned from his books such as (Al-Lama - Al-Tabasrah) saying: “This is not correct” and the word “This is wrong” and “this is false”. Among the objections of Sheikh Al-Shirazi is that he does not agree with the condition of having will in command, and according to him the issue of the command requires immediate and delay is a mistake for him and the correct one is does the command require immediate?. And that duty is given to the minimum that the name applies to, such as the required amount in bowing and prostrating.